Arab Students' Attitudes Toward Western Culture and Motivation to Learn English - Sadek, Gihane Ibrahim (2007)
A Master of Arts Thesis in Teaching English to Speakers of Other Languages (TESOL) Submitted to the College of Arts and Sciences by Gihane Ibrahim Sadek Entitled, "Arab Students' Attitudes Toward Western Culture and Motivation to Learn English," January 2007. Available are both Soft and Hard Copies of the Thesis.